The Relationship Between Morphometric Characteristics and The Weight of Tubuca forcipata (Subfamily: Gelasiminae) in The Mangrove Nature Reserve of Eastern Coast Resort Mendahara, Jambi Province - Auliaputri, Tazkiah; Ihsan, Mahya; Wulandari, Tia (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The objective of this study is to ascertain the pathogenic and antagonistic fungi that induce disease in avocado plants (Persea americana Mill), identify the antagonistic fungi with the greatest antagonism potential among a variety of antagonistic fungi, and elucidate the mechanism by which antagonistic fungi inhibit the growth of pathogenic fungi. From January to May 2023, this study was conducted in vitro at the Microbiology Laboratory, State University of Malang, employing a completely randomized design (CRD) comprising six replications and four interventions. The identification of mold was accomplished through macroscopically and microscopically descriptive analysis, followed by a comparison with the mold identification key book. The antagonism process was executed utilizing the dual culture method on the PDA medium, and the electron microscope (SEM) was employed to witness the antagonism mechanism. The research findings revealed that T. harzianum spp. and T. viride were identified as antagonist fungi, whereas C. aotearoa and C. gloeospoiroides were identified as pathogenic fungi. The antagonistic fungus T. viride exhibited the greatest degree of antagonism, impeding the growth of C. gloeospoiroides by 77.8%. Observed antagonism occurs when the hyphae of the antagonistic mold ensnare, entangle, and pierce those of the pathogenic mold, causing harm to the region surrounding the pathogenic mold's hyphae and subsequently impeding its growth